2009
DOI: 10.35536/lje.2009.v14.i2.a5
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of Pakistani Fruits in the World Market

Abstract: This paper examines the global competitiveness of Pakistan’s fruit exports (dates, mangoes, and oranges), using revealed comparative advantage (RCA). It also analyzes domestic consumption trends among selected fruits grown by major exporters. Our results indicate that Pakistan has a comparative advantage in fruit exports. Comparing the movement in comparative advantage indices for Pakistan with those of its main exporters/competitors demonstrates that Pakistan has a relatively high comparative and competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…To the best of our knowledge, there have been no separate data on the intake of these nutrients by Pakistani elderly. However it has been reported that mean intake of Ca, Fe and Zn by adults in the general Pakistani population is much lower than the recommendations [38]. Mean calcium, iron, and zinc intake in the present study seemed well within the intake range of most countries [39].…”
Section: Resultssupporting
confidence: 58%
“…To the best of our knowledge, there have been no separate data on the intake of these nutrients by Pakistani elderly. However it has been reported that mean intake of Ca, Fe and Zn by adults in the general Pakistani population is much lower than the recommendations [38]. Mean calcium, iron, and zinc intake in the present study seemed well within the intake range of most countries [39].…”
Section: Resultssupporting
confidence: 58%
“…To measure the export competitiveness of 10 major rice exporters in the global market, we used Balasa's (1965) and Vollrath's (1991) RCA competitive index. By following Akhtar et al (2009) and Abdullah et al (2015), in this study, we used two measures named as RCA and RCA#. In order to measure the competitiveness, Balassa (1965) had developed RCA measure.…”
Section: Methodsmentioning
confidence: 99%
“…Bender and Li (2002) had also used this sophisticated measure for international competitiveness. Akhtar et al (2009) and Abdullah et al (2015) have defined RCA and RCA# as:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Akhtar et al [16] have investigated the performance of footwear industry of Pakistan in comparison with China and India. While Mahmood [17] explores export specialization of Pakistan's non-agriculture production sectors, Akhtar et al [18] examined competitiveness of selected Pakistani fruits with major global fruit. On the other hand, Shahab and Mahmood [3] have analyzed the trade specialization in the leather products of Pakistan with other selected Asian economies-China, India and Iran.…”
Section: Literature Reviewmentioning
confidence: 99%